Islamic Caring Model on Increase Patient Satisfaction - Muh. Abdurrouf; Nursalam Nursalam; Purwaningsih Purwaningsih (Jurnal Ners, 2013)
Introduction: Patient satisfaction was important aspect that must be considered by health service providers, patients who were not satisfied will leave the hospital and be a competitor's customers so be able caused a decrease in sales of products/services and in turn could reduce and even loss of profit, therefore, the hospital must provided the best service so that it could increase patient satisfaction. The purpose of this study was to exams the effect of Islamic caring model on increase patient satisfaction.Methods: This study was used pre-experimental design, the respondents were 31 patients in the treatment group assigned Islamic caring and 31 patients with a kontrol group that were not given Islamic caring Inpatient Surgical Sultan Agung Islamic Hospital Semarang by using consecutive sampling techniques, patient satisfaction data collected through questionnaires and analyzed with Mann-Whitney test, as for finding out the Islamic caring for patient satisfaction were analyzed with spearmen's rho test.Results: The results showed that there was a significant influence of Islamic caring for perceived disconfirmation (p=0,000) there was a perceived disconfirmation influence on patient satisfaction significantly (p=0,000), there was a significant influence of Islamic caring for patient satisfaction in the treatment group with a kontrol group (p=0.001).Conclusion: Discussion of this study was Islamic caring model effect on the increase perceived disconfirmation and patient satisfaction, Perceived disconfirmation effect on patient satisfaction, patient satisfaction who given Islamic caring was increase, patients given Islamic caring had higher satisfaction levels than patients who not given Islamic caring. Suggestions put forward based on the results of the study of Islamic caring model could be applied in Sultan Agung Islamic Hospital as a model of nursing care, Islamic caring behavior can be learned and improved through training and commitment and could be applied in providing nursing care, further studies of other variables that had not been examined in accordance expectancy-disconfirmation theory according Wodruff and Gardial 2002 of comparison standard and satisfaction outcome.